Antidepressant and Anxiolytic Potentials of the Chewing Stick, Salvadora persica - Rajalakshimi Vasudevan; Geetha Kandasamy; Afaf Aldahish; Mona Almanasef; Moteb Khobrani; Eman Shorog; Kousalya Prabahar; Enas Mohammed Alsawaq; Shadma Wahab; M. Yasmin Begum; Premalatha Paulsamy (Journal of Tropical Medicine, 2023)
Purpose and Objectives. The quest for psychoactive plants possessing therapeutic potential has evolved emerging interest. Salvadora persica (Sp), belonging to the Salvadoraceae family, known as miswak, is a medicinal plant; most of its published research is on oral health, with promising antimicrobial, anti-inflammatory, and antiproliferative activity. However, given its widespread use, only few studies are associated with its potential neuropharmacological effect. Therefore, this study aims to assess the possible anxiolytic and antidepressant effects of Salvadora persica using animal models. Materials and Methods. Salvadora persica stem bark was extracted with two different solvents, i.e., ethyl acetate and water, and preliminary phytochemical screening was performed. Two behavioral models were used: an elevated plus maze test (EPM) and the light and dark model test for anxiolytic parameters, and a forced swim test (FST) for antidepressant effects. Healthy mice weighing 18−40 gms were treated orally in four groups (n = 6), i.e., negative control treated with normal saline and positive control with 1 mg/kg diazepam (EPM) and 30 mg/kg fluoxetine (FST), and the test groups were treated with 500 mg/kg of aqueous and ethyl acetate Sp extract. The number of entries and duration spent in the open arm for 5 minutes were the parameters for evaluating the anxiolytic activity (EPM). Duration of immobility was measured for 5 min in the FST model. Results. In EPM, both the Sp extracts significantly (p < 0.005) increased the number of entries and the time spent in the open arms and was much similar to those of diazepam. Similarly, these extracts and fluoxetine significantly (p < 0.005) decreased the immobility time in FST. Conclusion. The results suggest the therapeutic potential of Salvadora persica an alternative in the management of comorbid anxiety and depression.